Nasopharyngeal Carcinoma Presented with Right Upper Limb Weakness: A Case Report - Z, Zamzuri; SY, Mohd Adham; A, Mohamad Saufi; AA, Azian; MA, Mohamed Azril; AR, Azlina (IIUM Medical Journal Malaysia, 2012)
Nasopharyngeal carcinoma (NPC) is a malignant neoplasm arising from the mucosal epithelium of the nasopharynx, mainly within the lateral nasopharyngeal recess or Fossa of Rosenmuller. Distant metastasis to the cervical spine is the least common site in the vertebral system. This is a case of a 37-year-old lady with stage IV C nasopharyngeal carcinoma with local extension to the cervical spine who presented with right upper limb weakness.